Anterograde Intramedullary Nailing without Bone Grafting for Humeral Shaft Nonunion Associated with Early Exploration of Secondary Radial Nerve Palsy: A Case Report - Dan Viorel Nistor; Răzvan Marian Melinte; Romana von Mengershausen (MDPI AG, 2024)
Background: Humeral shaft fractures are relatively common. Complications associated with this type of fracture and its treatment include nonunion and radial nerve palsy. Plate osteosynthesis with autologous bone grafting is considered the gold standard for treating nonunion. However, bone grafts might not always be necessary in cases of hypertrophic nonunion, and treatment should be tailored to the specific type and characteristics of the nonunion. The treatment of radial nerve palsy is debated, with some favoring expectant management based on the nerve's ability to regenerate, and others preferring early surgical exploration to prevent possible lasting nerve damage. Methods: We present the case of a 46-year-old male patient with a six-year-old humeral shaft fracture resulting in hypertrophic nonunion. We treated the nonunion with anterograde intramedullary nailing without bone grafting. Postoperatively, the patient developed severe radial nerve palsy. After repeated electrophysiological studies, a decision was made to surgically explore the nerve 10 days after the nonunion surgery. The nerve was subsequently found to be intact and treated with neurolysis. Results: Bony union was shown at six months after nonunion surgery. Four months after the nonunion surgery, the patient started to show clinical signs of nerve recovery, and at 12 months he achieved nearly full clinical recovery of radial nerve function. Conclusions: Anterograde intramedullary nailing without autologous bone grafting may be considered an option for treating hypertrophic nonunion. The management of radial nerve palsy requires effective cooperation and communication between patient and physician. Further research is necessary to be able to better predict nerve recovery.